UJI MINUMAN SARI PEPAYA (Carica papayaL.) PROBIOTIK TERHADAP KADAR KOLESTEROL TOTAL PADATIKUS PUTIH (Rattus norvegicus) JANTAN GALUR SPRAGUE DAWLEY - Herson Cahaya Himawan; R. Haryo Bimo Setiarto; Nandani Dwi Octavia (Jurnal Farmamedika (Pharmamedika Journal), 2017)
Probiotic drink can be used as antihipercholesterolemia therapy. One potential ingredient for probiotic drink is papaya (Carica papaya L.) which can be fermented using lactic acid bacteria. The purpose of this research is to find out whether lactic acid mixed bacteria lactate acid bacterium formula Lactobacillus bulgaricus: Lactobacillus acidophilus : Streptococcus thermophilus with a ratio of 1: 1: 1 produced into probiotic papaya juice drink by fermentation can reduce total cholesterol levels in white rats (Rattus norvegicus) male Sprague Dawley strain. This research was conducted in Food Microbiology Laboratory of LIPI Biology Research Center. The papaya juice is fermented using a mixed culture formulation consisting of Lactobacillus bulgaricus: Lactobacillus acidophilus: Streptococcus thermophilus ;. Test animals were grouped into three groups: negative control, positive control and probiotic papaya juice, each group consisting of nine rats. The results showed that. After testing the total cholesterol reduction activity, it was found that probiotic papaya juice drink can reduce high cholesterol to normal with a decrease percentage of 17.51%. Probiotic papaya juice drinks can be applied to antihipercholesterolemia therapy in humans at doses of 55.56 ml per day.